English Teachers’ Challenges and Method in Building Learners’ Speaking Skills During Merdeka Curriculum in Junior High School - Ningsih, Ina Wahyu Priyanti; Ahmad Tauchid, Ahmad; Putri, Nanin Verina Widya (English Education and Literature Journal (E-Jou), 2024)
This research is based on the problems teachers have faced. where teachers must be able to create a more effective and active learning atmosphere. In the independent curriculum, the teacher is a facilitator who helps students to achieve learning goals. In this case, a learning strategy is very necessary to support learning achievement. The urgency of this research raises existing problems at this school this problem will be followed up later That. the main aim of this research is to explain the method used in special learning for teaching English with the Merdeka curriculum in junior high schools and also the challenges as an English teacher in the Merdeka curriculum. This research will utilize descriptive qualitative research. This research will later be carried out at one of the junior high schools in Bojonegoro in the 2023-2024 academic years. In this research, the researcher will use observation, an interview instrument to collect the data. In this research, the researcher will analyze the data using three concurrent flows including data reduction, data display, and drawing conclusion/verification. the result of previous chapter, there are six challenges faced by teachers, namely method do teachers, mother tongue, motivation, lack of vocabulary, facilities, learning material. All of these challenges have been overcome well, namely by providing vocabulary since sitting in the seventh grade class, then providing student motivation during learning, using strategy group discussions to develop interaction between friends. In learning, of course, it is not always as expected, there are many obstacles faced by teachers. By providing motivation when learning, it is hoped that students will be able to be more active in studying